Summer Hydrography and Circulation in Storfjorden, Svalbard, Following a Record Low Winter Sea‐Ice Extent in the Barents Sea. Issue 2 (10th February 2023) - Vivier, Frédéric; Lourenço, Antonio; Michel, Elisabeth; Skogseth, Ragnheid; Rousset, Clément; Lansard, Bruno; Bouruet‐Aubertot, Pascale; Boutin, Jacqueline; Bombled, Bruno; Cuypers, Yannis; Crispi, Olivier; Dausse, Dennis; et al.
Abstract: Storfjorden, Svalbard, hosts a polynya in winter and is an important source region of Brine‐enriched Shelf Water (BSW) that, if dense enough, feeds the Arctic Ocean deep water reservoir. Changes in the BSW production may thus have far‐reaching impacts. We analyze the water mass distribution and circulation in Storfjorden and the trough south of it, Storfjordrenna, using hydrographic sections occupied in July 2016, following a winter characterized by the lowest ice coverage recorded in the Barents Sea. These observations reveal an unusual hydrographic state, characterized at the surface by the near absence of Melt Water and Storfjorden Surface Water, replaced by a saltier water mass. At depth, BSW (maximum salinity of 34.95) was found from the bottom up to 90 m, above the 120‐m deep sill at the mouth to Storfjordrenna. However, no gravity driven overflow was observed downstream of the sill: the dome of BSW remained locked over the depression in a cyclonic circulation pattern consistent with a stratified Taylor column. Observations further reveal a previously unreported intrusion of Atlantic Water (AW) far into the fjord, promoting isopycnal mixing with entrapped Arctic Water. This intrusion was possibly favored by positive wind stress curl anomalies over Svalbardbanken and Storfjordrenna. The bottom plume exiting Storfjordrenna was weak, carrying Polar Front Water rather than BSW, too light to sink underneath the AW layer at Fram Strait. Whether Storfjorden switched durably to a new hydrographic state, following the observed Atlantification of the Barents Sea after 2005, remains to be established. Plain Language Summary: Storfjorden, east of Spitsbergen, plays an important role in Arctic Ocean climate through formation of dense water as salt is added to the ocean when sea ice forms. This dense water accumulates in winter before spilling toward the deep ocean into autumn, fueling the global ocean's circulation. We analyze observations from a research cruise in July 2016, following a winter season characterized by the lowest ice coverage in the Barents Sea ever recorded. These observations reveal striking differences from previous reports, which are mostly based on data prior to the 2005 regime shift in the Barents Sea characterized by warmer temperature and reduced ice cover, an expression of its "Atlantification" reported by many authors. First, the expected overflow of the locally formed dense water was absent. The latter, less saline than usual, was instead trapped in Storfjorden suggesting an intermittent discharge regime usually observed in the fall. Another notable observation is the intrusion of Atlantic Water far inside the fjord. Such a flooding episode, increasingly frequent in the fjords of the west coast of Spitsbergen, is previously unreported in Storfjorden. These observations made in the wake of an exceptionally mild winter could prefigure more permanent changes in this important region. Key Points: Changes in the hydrography and circulation in Storfjorden a decade after a regime shift in the Barents Sea linked to its Atlantification The less saline Brine‐enriched Shelf Water remained entrapped in Storfjorden within a cyclonic circulation pattern with no overflow Storfjorden was flooded with Atlantic Water, promoting isopycnal mixing with Arctic Water and the local formation of East Spitsbergen Water